Combined effect of plant-based protein supplementation with resistance training on muscular strength, protein catabolism, immune functions and bone metabolism markers in adult males - Ahmad, Azaizirawati (2018)
Combination of protein supplementation and resistance training is known to develop muscle bulk for physical appearances and strength gain. Plant-based protein has been used to a lesser extent than animal-based protein, to increase muscle strength and reduce protein catabolism. Furthermore, resistance training has been shown to enhance immune function and bone density compared to endurance training. The purpose of this study was to investigate the combined effect of plant-based protein supplementation which consists of soy and pea protein with resistance training on muscular strength, protein catabolism, immune functions and bone metabolism markers in adult males.Twenty eight sedentary adults male (Mean±SD age: 22.72 ± 3.17 height: 169.40± 5.76 weight: 68.04 ± 8.97 BMI: 23.70 ± 2.95) volunteered for testing before and after an 8-week of study intervention. Muscular strength was determined by using isokinetic dynamometer and blood taking procedure were performed for protein catabolism, immune function and bone metabolism markers. Participants were randomly assigned into four groups of either plant-based protein combined resistance training (PBPEX), plant-based protein alone (PBP), resistance training alone (EX) or control (C). Participants in PBPEX and PBP groups consumed 16g plant-based protein consists of soy and pea protein while participants in EX and C groups consumed 16g placebo consists of maltodextrin. All supplements were given in the form of white powder in sealed sachets and to be diluted in 150ml of plain water. The supplements were consumed every day in the morning for 8 weeks.Participants in PBPEX and EX groups performed three sets of 4-6 repetitions, 3 times per week for 8 weeks, of supervised resistance training that consisted of seven types of total body exercises at 60-70% intensity of one repetition maximum (1-RM). During training days, participants in PBPEX and EX groups consumed the supplement immediately after training session. All data were analysed using repeated measures ANOVA. PBPEX could significantly increase (p<0.01) more isokinetic muscular strength parameter, i.e knee and shoulder flexion peak torque compared to EX groups. For protein catabolism measures, PBP showed significantly higher level (p<0.05) in serum urea and blood urea nitrogen (BUN) than PBPEX, EX and C groups respectively. There were no significant differences in immune function parameters between pre- and post- tests in all the groups. For bone metabolism markers, no statistically significant changes were observed in bone formation and resorption markers. Combination of plant-based protein and resistance training showed greater beneficial effects on enhancing muscular strength than resistance training alone. For protein catabolism, plant-based protein combined with resistance training seems to have potential in attenuating the increase of protein catabolism induced by plant-based protein alone. There were significant effects on immune function parameters and bone metabolism markers with combination of plant-based protein and resistance training. Combination of plant-based protein supplementation and resistance training elicited greater beneficial effects on muscular strength than resistance training alone and plant-based protein supplementation alone. Therefore, combined plant-based protein with resistance training may be recommended as a guideline in planning exercise and nutritional programme for sedentary male adults.